Effects of students' and schools' characteristics on mathematics achievement: findings from PISA 2006 - Demir, Ibrahim; Kilic, Serpil; Unal, Hasan (ELSEVIER SCIENCE BV, 2010)
This study explored the effects on mathematics achievement of students' and Schools' characteristics. To do that, gender, computer use for internet or entertainment, self-confidence in high level computer tasks, school types and economic, social and cultural status of students' families are analyzed with detailed. The sample was prepared from students who participated in Programme for International Student Assessment (PISA) 2006 in Turkey. The estimates of PISA mathematics performance and questionnaire responses of 4942 15 year-old Turkish students in 160 schools were analyzed via multilevel analysis. Also, it was shown that frequencies of the reasons of students' computer use. Two-level model was used to estimate coefficients and modeled differences across school types. Results from this study indicated that male students, students who have high self-confidence to use computer, students who have high economic, social and cultural status and schools which have quality educational resources have better scores in mathematics. However, female students and schools which have high student teacher ratio have lower score in mathematics. Furthermore, students, particularly female students, need greater motivation to use computers and teachers should integrate computer within mathematics and programs. Also, higher socio-economic and cultural status of the family, higher educational background of the parents and students who find mathematics subjects important are the factors that increase mathematics performance too. As a result of this study, it is shown that some characteristics of student and schools, especially gender and quality educational resources, have a positive effect on mathematic achievement. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Multilevel model; gender; self-confidence to use computer; mathematics achievement; PISA; Education & Educational Research